2021
DOI: 10.3390/cells10082083
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fibromodulin and Myostatin to Regulate Skeletal Muscle Aging: An Opposite Regulation in Muscle Aging, Diabetes, and Intracellular Lipid Accumulation

Abstract: The objective of this study was to investigate fibromodulin (FMOD) and myostatin (MSTN) gene expressions during skeletal muscle aging and to understand their involvements in this process. The expressions of genes related to muscle aging (Atrogin 1 and Glb1), diabetes (RAGE and CD163), and lipid accumulation (CD36 and PPARγ) and those of FMOD and MSTN were examined in CTX-injected, aged, MSTN−/−, and high-fat diet (HFD) mice and in C2C12 myoblasts treated with ceramide or grown under adipogenic conditions. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Some natural compounds [95][96][97] and inhibitory peptides targeting MSTN [21,98], such as Ac-MIF1 and Ac-MIF2-NH2, have been reported to inhibit the effect of MSTN significantly and enhance cell proliferation [99]. Additionally, in vivo and in vitro data showed that FMOD prevents muscle aging by decreasing the activity of MSTN protein [92]. These findings indicate that MSTN gene sequence modification and MSTN inhibition are good strategies for the mass production of cultured meat from agricultural animals.…”
Section: Myostatinmentioning
confidence: 95%
See 1 more Smart Citation
“…Some natural compounds [95][96][97] and inhibitory peptides targeting MSTN [21,98], such as Ac-MIF1 and Ac-MIF2-NH2, have been reported to inhibit the effect of MSTN significantly and enhance cell proliferation [99]. Additionally, in vivo and in vitro data showed that FMOD prevents muscle aging by decreasing the activity of MSTN protein [92]. These findings indicate that MSTN gene sequence modification and MSTN inhibition are good strategies for the mass production of cultured meat from agricultural animals.…”
Section: Myostatinmentioning
confidence: 95%
“…Myostatin (growth and development factor-8, MSTN) is present in SM, and muscle mass in MSTN-null mice was reported to be dramatically enhanced due to increased muscle fiber levels (hyperplasia) and sizes (hypertrophy) [91,92]. Furthermore, the double-muscled phenotype in cattle has been linked to the MSTN gene.…”
Section: Myostatinmentioning
confidence: 99%
“…FMOD is known to be actively involved in the assembly of ECM and was recently reported to be a novel regulator of MSTN during myoblast differentiation by regulating the transcriptional activities of MSTN and other myogenic marker genes, which include myogenin (MYOG) and myosin light chain 2 (MYL2) ( Lee et al, 2016 ). FMOD suppresses muscle aging by negatively regulating the MSTN gene or reducing the action of MSTN protein, while MSTN promotes muscle aging by positively regulating the expressions of the Atrogin1, CD36, and PPAR genes in muscle tissues ( Lee et al, 2021a ).…”
Section: Mstn Inhibitionmentioning
confidence: 99%
“…We previously investigated a number of ECM proteins that are involved in the regulation of myogenesis, including FMOD [10,11], matrix Gla protein [12], and dermatopontin [13]. FMOD slows muscle aging by suppressing the MSTN gene or decreasing MSTN protein activity, whereas MSTN promotes muscle aging [14]. Co-immunoprecipitation studies revealed that FMOD interacts directly with MSTN during myoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%